Solomon Islands Coconut Value Chain Analysis - Young, David; Pelomo, Moses (World Bank, Washington, DC, 2014)
The report comprises five sections: section two describes Solomon Islands Government's (SIG) national and sector policies and strategies, the state of infrastructure and transport, relevant institution and regulatory frameworks activities of development partners involved in the coconut industry; section three provides an overview of global and domestic trends in prices, production and productivity of coconut products; section four provides an overview of the copra value chain and a snapshot of costs, revenues and gross margins accruing to smallholders, traders and exporters at each stage of the value chain; section five provides an overview of key challenges in development of the Solomon Islands coconut value chain; and section six concludes the main findings of the value chain analysis and makes recommendations around improving agriculture services and enhancing value chains.